Study Of The Effect Of Urban Walls On Social Interactions - Aboutaleb, Narges; Mianroudi, Sahar Hasani; Movahed, Farzad Saberi (The Turkish Online Journal of Design Art and Communication, 2016)
Facade of a building is effective in the shape of a city. These facades shape the view of city when they put together. The first panel introduces the city to travelers and tourists, that is why it is particularly important to introduce any area. Urban walls are the most important elements that affect the relationship between people and the improvement of living space, these walls bring their activities as well as public spaces and show culture of the people that unfortunately today abnormalities and visual disturbances have transformed the shape, form, color and materials of building facades, and view of cities. It's a descriptive study that it has been tried to define the urban facade and factors affecting the urban facade and walls. It also studies the concept of social interactions and impact of the city walls on interactions and relationships between people and expresses how visual disturbances can cause bodies to be heterogeneous and anonymous environment.
Keywords: City Walls; Facades; Culture; Social Interaction; Visual Disturbances